Neolithic water management and flooding in the Lesser Caucasus (Georgia). (1st October 2018) - Ollivier, V.; Fontugne, M.; Hamon, C.; Decaix, A.; Hatté, C.; Jalabadze, M.
Abstract: River management is generally thought to have started at 5500 cal. BC within the development of eastern Neolithic societies. In the Lesser Caucasus, evidence of early river management has been discovered around the famous Neolithic sites of Shulaveri, Gadachrili Gora, and Imiris Gora in Georgia. Here we report a preliminary data set indicating that river management was set up at 5900 cal. BC leading to the flooding, destruction, and local abandonment of the hydraulic infrastructures of the Gadachrili village between 5750 and 5430 cal. BC. The hydraulic infrastructures were developed during a more humid period encompassing the 8200 cal. BP (6200 cal. BC) climatic event, probably to optimize agricultural yield. It potentially led to the first prehistoric engineering accident for which there is evidence, which may have been followed by the reorganisation of the occupation and/or to architectural modifications. Highlights: In the Lesser Caucasus, some evidences of Early Neolithic river management have been discovered. We report a preliminary data set indicating that the river management was made 5900 cal. BC ago and led to Neolithic village flooding, destruction and local abandonment of the hydraulic infrastructures between 5750 and 5430 cal. BC. We carried out isotopic analyzes on the seeds in order to characterize or not the occurrence of irrigation. We highlight the possibility of a development in the Caucasus of the oldest known water management practices. We also present an original focus on the potential effects of torrential palaeo-floods in Neolithic water management structures and riparian habitats.